2019
DOI: 10.1007/s10554-019-01563-3
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial adaptation after surgical therapy differs for aortic valve stenosis and hypertrophic obstructive cardiomyopathy

Abstract: Surgical therapies in aortic valve stenosis (AVS) and hypertrophic obstructive cardiomyopathy (HOCM) aim to relief intraventricular pressure overload and improve clinical outcome. It is currently unknown to what extent myocardial adaptation concurs with restoration of intraventricular pressures, and whether this is similar in both patient groups. The aim of this study was to investigate changes in myocardial adaptation after surgical therapies for AVS and HOCM. Ten AVS and ten HOCM patients were enrolled and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…Thus, they would not have captured the development of systolic dysfunction or death-equivalent outcomes of cardiac transplantation or LVAD implantation (30 patients in our cohort). Nonetheless, 2 smaller studies also identified an increased risk of developing impaired LV function after SRT 20 and emphasized that the duration of follow-up needs to be relatively long, at least 8 to 10 years, to capture this adverse remodeling. 21 This time frame is supported by our current findings.…”
Section: Incident Development Of Systolic Dysfunctionmentioning
confidence: 99%
“…Thus, they would not have captured the development of systolic dysfunction or death-equivalent outcomes of cardiac transplantation or LVAD implantation (30 patients in our cohort). Nonetheless, 2 smaller studies also identified an increased risk of developing impaired LV function after SRT 20 and emphasized that the duration of follow-up needs to be relatively long, at least 8 to 10 years, to capture this adverse remodeling. 21 This time frame is supported by our current findings.…”
Section: Incident Development Of Systolic Dysfunctionmentioning
confidence: 99%
“… 4 Another study demonstrated worsening of septal systolic strain rates and no improvements in global and regional longitudinal strain after septal myectomy despite improvement in exercise capacity in 10 patients with obstructive HCM. 32 In this study, the amount of late gadolinium enhancement showed no significant increase after septal myectomy. 32 The reduction of the hypertrophied LV and wall thinning after septal myectomy may also have contributed to the impaired LV longitudinal systolic function.…”
Section: Discussionmentioning
confidence: 45%
“… 32 In this study, the amount of late gadolinium enhancement showed no significant increase after septal myectomy. 32 The reduction of the hypertrophied LV and wall thinning after septal myectomy may also have contributed to the impaired LV longitudinal systolic function. However, there was no difference in the septal wall strain in our study.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…In order to understand the differences in remodeling after afterload removal in myocardium with intrinsic myocardial abnormality vs. that with presumably normal intact intracellular pathways, it is interesting to consider the structural and functional recovery after myectomy for oHCM and aortic valve replacement (AVR) for aortic valve stenosis, an extrinsic cause of hypertrophy ( 58 ). A small prospective study of 10 patients with oHCM and 10 patients with severe aortic stenosis (AS) were examined with echocardiography, CMR, and exercise testing.…”
Section: Myocardial Remodeling In Hcmmentioning
confidence: 99%